Total knee arthroplasty reduces the risk of mortality in osteoarthritis patients up to 12 years: A Korean national cohort longitudinal follow-up study. (18th February 2020) - Choi, Hyo Geun; Kwon, Bong Cheol; Kim, Joong Il; Lee, Joon Kyu
Introduction: Mortality rates and causes of death after total knee arthroplasty (TKA) are of great interest to surgeons. However, there is a shortage of studies regarding those of the Asian population. The aim of this study was to compare the mortality rate and causes of death in patients after TKA to the general population. Methods: National sample cohort data from the Korean Health Insurance Review and Assessment Service were used. In this study, 1:4 matched patients after TKA (TKA group: 5072) and general participants (control group: 20, 288) were selected as subjects. Their average follow-up duration was 57.2 months ranging from a year up to 12 years. The matches were processed for age, gender, income, region of residence, and past medical history. Mortality rates and causes of death were compared between groups. Regarding the mortality rates, we also performed subgroup analyses according to age. Results: Adjusted hazard ratio (HR) of the TKA group for mortality rate was less than 1 with significance (adjusted HR = 0.61 (95% confidence interval = 0.54–0.70, p < 0.001)). The ratios were less than 1 for both age groups (<70 and ≥70 years), respectively; however, for patients under 70, they were insignificant. Among the 11 major causes of death, the circulatory disease showed the most significantly reduced mortality rate for the TKA group compared to the control group. The neoplasm was the only other cause with a significantly reduced mortality rate for the TKA group. Conclusion: The mortality rate in the TKA group was significantly lower than in the control group up to 12 years after the surgery in Korea. Among the major causes of death, circulatory disease and neoplasm showed a significant reduction in the mortality rate of the TKA group compared with the control group.